If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4y + 5z = 9 Solving 3x + -4y + 5z = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 3x + -4y + 4y + 5z = 9 + 4y Combine like terms: -4y + 4y = 0 3x + 0 + 5z = 9 + 4y 3x + 5z = 9 + 4y Add '-5z' to each side of the equation. 3x + 5z + -5z = 9 + 4y + -5z Combine like terms: 5z + -5z = 0 3x + 0 = 9 + 4y + -5z 3x = 9 + 4y + -5z Divide each side by '3'. x = 3 + 1.333333333y + -1.666666667z Simplifying x = 3 + 1.333333333y + -1.666666667z
| https://www.vle.mathswatch.com/images/questions/question3802.pn | | 3x-33=21 | | 130=-18-(7y-8) | | 7x-56=5x+10 | | -4x+15=16x+20 | | 4x^2+4x+4=x+3 | | 6x^2-38x=-32 | | 9+u=-3 | | 0=20t+5t^2-125 | | 26=15-(11a+22) | | 30x^2+17*x+2=0 | | 19/20y*5/6x | | 4x+1=9+4x | | 17v-(7v-3)=13 | | X+2=x^2-4x+1 | | 10k-(6k-14)=2 | | -3y-8=16 | | 6x^3-48x= | | .5x+3+2x-12=31 | | 4x-3*3.14=7x+6*3.14 | | 41=48-8(-3-2w) | | 14g=46 | | -42=25x-4(4x-3) | | 2.4x(-0.8)=5x(-2) | | 2.4x(-0.8)=5y(-2) | | 24d=-0.5 | | -58=14q-2(3q+1) | | X=2,x=6/7 | | 6x-8+4x+6+5x+16+5x+16=360 | | (X-2y)dx-(2x+5y)dy=0 | | 14c=-11 | | 2x^3+7=61 |